The Effect of Facebook on Academic Performance for Undergraduate Students at Charmo University - M-Saleh, Hardi M.; Abdul, Zrar Kh.; Ameen, Azad Abdullah (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
Facebook occupies an important part of people's time and life due to the recent developments in the field of communication technologies (CT). This paper aims at investigating the Facebook impact (FI) on undergraduate students at Charmo University. Moreover, Facebook also has a great impact on students' life studies at universities. However, in addition to its benefits, Facebook also has some side effects on students' life study. In regard to data collection, an online survey was used in which 15 questions were answered by 100 participants from different faculties at Charmo University. The data collection process was conducted from First of March to 30 of April 2016. The program of SPSS was used to analyze the results of the survey. The results of the current study shows that students spend a significant amount of their times on using Facebook.